The Jewish Presence in Two Short Stories by Samuel Rawet: An Analysis of A Nova Sinagoga and A Prece - Aparecido Valentin, Leandro Henrique [UNESP] (Univ Federal Minas Gerais-ufmg, 2017)
This paper analyzes A nova sinagoga and A prece, which are likely to be the first short stories with a Jewish theme Samuel Rawet ever published. Focusing both on formal and thematic aspects of the short stories under study, the analysis developed highlights the use of certain narrative techniques distinct from each other in such texts that points, to some extent, to an enhancement of Rawet's crafting in the beginning of his career as a storyteller.
Keywords: Samuel Rawet; A nova sinagoga; A prece